Neutrophilic extracellular traps and association with serious pulmonary complications at Covid-19 (Revista Contexto & Saúde, 2023)
The present study aims to define an association between the formation of NETs and the development of pulmonary disorders in Covid-19, as well as to explore its performance as a biomarker in the disease. This is an integrative literature review, through the survey of scientific articles in the following databases: PubMed, Latin American and Caribbean Literature in Health Sciences (Lilacs) and Online Medical Literature Analysis and Recovery System (Medline) Based on the inclusion and exclusion criteria, 18 articles were selected for this review. Activation of neutrophils and formation of NETs have been defined as risk factors for mortality in Covid-19 patients. The release of NETs is fully correlated with the severity of the pulmonary pathology. Throughout this study, it is concluded that the formation of excess NETs is present in severe cases of COVID-19 and associated as a biomarker of several complications such as thrombosis and coagulopathies.
Keywords: NETs; COVID-19; Coronavirus; Lung Injury.